Geometrical entities for analysis of geographical entities in Geographic Information Systems using oriented object data modeling - Espinoza Pereyra, Marcos Fidel (2018)
This paper proposes a methodology (using Object-oriented data modeling) to use geometrical entities such as “Point” (Punto in Spanish), “Polyline” (Polilínea in Spanish) and “Polygon” (Polígono in Spanish) using an abstract way using their properties and some functions upon themselves, in order to use them in Geographic Information Systems (GIS) Programming in an easier way to represent geographical entities. The last part you can see some simple examples about performing these abstractions.